Attitudes Toward Psychiatry Among Medical Students With a Psychiatric Major at Chongqing Medical University - Li, Xiao; Ai, Ming; Chen, Xiaolu; Gan, Yao; He, Jinglan; Tian, Yu; Zhai, Jian; Yang, Haoling; Kuang, Li (Frontiers in Psychiatry, 2022)
Objectives To understand the attitudes of medical students with a psychiatry major toward psychiatry at Chongqing medical university in China and to find out factors influencing students' career choice. Methods The present study used an online web survey tool to assess the attitudes toward psychiatry amongst 422 students majoring in psychiatry at Chongqing medical university in China using sociodemographic and Attitudes Toward Psychiatry-30 items (ATP-30) scales. Descriptive statistics and logistic regression analysis were used to examine associated factors. Results Three hundred and sixty-nine students (87%) answered the questionnaire. Nearly 54.5% of participants had overall positive attitudes to psychiatry and 80.8% thought psychiatrist could be a career choice. Of the students, 5.1% showed that they did not want to be a psychiatrist while the remaining 14.1% were undecided. The first and fifth year students showed less desire to be a psychiatrist (74.3 and 69.8%, respectively); the highest percentage recorded is of the third year (90.6%). Female participants, in contact with patients suffering from mental illness, were willing to study psychiatry as a master degree and see good prospects were positive factors in choosing psychiatry as a career. Conclusions Students generally have good expectations toward psychiatry, but different opinions are also held and the field is still faced with various challenges in order to provide more psychiatrists.